STUDY COMBINATION OF N-HEXANE EXTRACT OF BINAHONG (ANREDERA CORDIFOLIA (TEN.) V. STEENIS) LEAVES WITH ANTI-TUBERCULOSIS DRUGS AGAINST MYCOBACTERIUM TUBERCULOSIS - Ayu Eka Pitaloka, Dian
The resurgence of tuberculosis caused by Mycobacterium tuberculosis (Mtb) is associated with the rapid spread of multidrug-resistant, therefore the development of new antimycobacterial agents is necessary especially from natural product. Binahong (Anredera cordifolia (Ten) v.Steenis) leaves are known to have antimicrobial activity in a variety of bacteria such as Escherichia coli, B.cereus, B.subtilis, and Methicillin-susceptible Staphylococcus aureus with MIC values below 300 µg / mL. Based on this information, binahong leaves are potential for further development as antimycobacterial agent. The aim of this study was to evaluate the antimycobacterial activity extracts of binahong leaves when it using alone and combination with tuberculosis drugs. Extraction was done by three different solvent with increasing polarity. Mtb H37Rv sensitive strain, streptomycin-rifampicin resistant strain, and isoniazid-ethambutol resistant strain were evaluated by susceptibility test using a serial number of extract (50 µg/mL– 1000 µg/mL). MICs was read as minimum concentration of drugs that completely inhibit visible growth of organism. Study combination of extract with antituberculosis drug were determined in Lowenstein Jensen media by calculating the Fractional Inhibitory Concentration Index (FICI). The results showed that nhexane extract of binahong leaves has greater activity to inhibit the growth of Mtb compare to other extracts. It was showed by lower MIC values of n-hexane extract compare to other extract of binahong leaves. It was 500 µg/mL for H37Rv sensitive strain or rifampicin-streptomycin resistant strain and 250 µg/mL for isoniazid-ethambutol resistant strain. The combination of n-hexane extract and antituberculosis drugs displayed synergistic interaction and no antagonism result from the combination was observed for both drug-sensitive and drug-resistant strain of Mtb. Thin Layer Chromatography was used to identified ursolic acid and oleanolic acid in extract of binahong leaves and good separation was achieved by using mixture of toluene, ethyl acetate, and formic acid (30:15:1 v/v/v) as mobile phase. Rf value for ursolic acid was 0.59 and for oleanolic acid was 0.70.